Pemodelan Hubungan Hujan, Limpasan dan Kapasitas Erosi pada Suatu DAS yang Masuk ke Palung Sungai - Hang Tuah Salim; M. Syahril Badri Kusuma; Nazili Nazili (Journal of Mathematical and Fundamental Sciences, 2006)
This paper present the results of the mathematical model study on the relation between rain fall pattern, surface run off flows and land erodibility of a catchment area and river sedimentation. The influences of catchment area characteristics such as land use, soil behavior, topography condition and other related physical condition is encountered. Surface flow assessment is done at each sub catchment area by using mathematical model named ANSWER. Case study on Cipeles Catchmen area had shown that land use and rain fall pattern are the main parameter. Good agreement between model result and observation is shown on surface run off flow and sediment pattern, but there is still significant inaccuracy in its magnitude. This inaccuracy could be minimized not only by improving the model but also using a better data calibration, such as highly correlated rain fall and river discharge data with catchment area land use condition.